Comparing Glycaemic Benefits of Active Versus Passive Lifestyle Intervention in Kidney Allograft Recipients: A Randomized Controlled Trial. Issue 7 (July 2020) - Kuningas, Kulli; Driscoll, Joanne; Mair, Reena; Smith, Helen; Dutton, Mary; Day, Edward; Sharif,; Adnan
Abstract : Background: New-onset diabetes is common after kidney transplantation, but the benefit of lifestyle intervention to improve glucose metabolism posttransplantation is unproven. Methods: We conducted a single-center, randomized controlled trial involving 130 nondiabetic kidney transplant recipients with stable function between 3 and 24 months post-transplantation. Participants were randomly assigned in a 1:1 ratio to receive active intervention (lifestyle advice delivered by renal dietitians using behavior change techniques) versus passive intervention (leaflet advice alone). Primary outcome was 6-month change in insulin secretion, insulin sensitivity, and disposition index. Secondary outcomes included patient-reported outcomes, cardiometabolic parameters, clinical outcomes, and safety endpoints. Results: Between August 17, 2015 and December 18, 2017, 130 individuals were recruited, of whom 103 completed the study (drop-out rate 20.8%). Active versus passive intervention was not associated with any change in glucose metabolism: insulin secretion (mean difference, −446; 95% confidence interval [CI], −3184 to 2292; P = 0.748), insulin sensitivity (mean difference, −0.45; 95% CI, −1.34 to 0.44; P = 0.319), or disposition index (mean difference, −940; 95% CI, −5655 to 3775; P = 0.693). Clinically, active versus passive lifestyle intervention resulted in reduced incidence of posttransplantation diabetes (7.6% versus 15.6%, respectively, P = 0.123), reduction in fat mass (mean difference, −1.537 kg; 95% CI, −2.947 to −0.127; P = 0.033), and improvement in weight (mean difference, −2.47 kg; 95% CI, −4.01 to −0.92; P = 0.002). No serious adverse events were noted. Conclusions: Active lifestyle intervention led by renal dietitians did not improve surrogate markers of glucose metabolism. Further investigation is warranted to determine if clinical outcomes can be improved using this methodology. Abstract : Supplemental Digital Content is available in the text.